THE PROBLEM OF VENEREAL DISEASE IN TEHERAN - AA. Alemi; M. Subramanian (Tehran University of Medical Sciences, 1975)
Rapid spread of venereal diseases in advanced countries has prompted the authors to undertake this study on venereal diseases in Iran, a fast growing country, with a view to finding ways for dealing with these diseases. Data available at the VD centre in Teheran, the rapidly developing capital of Iran, have been used for this preliminary study. A retrospective analysis of available data for the period 1964-1973 has shown that VD cases in Iran has been increasing and that composition of clientele of VD centre has substantially changed over time. The need for an effective and efficient control programme based on a time limited epidemiological-behavioural survey of general population and on functional analysis of health units presently catering to the demand of population has been brought out.